2009
DOI: 10.1152/ajpheart.01120.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical work and energetic analysis of eccentric cardiac remodeling in a volume overload heart failure in rats

Abstract: Eccentric cardiac remodeling seen in dilated cardiomyopathy or regurgitant valvular disease is a well-known process of heart failure progression, but its mechanoenergetic profile has not been yet established. We made a volume overload (VO) heart failure model in rats and for the first time investigated left ventricular (LV) mechanical work and energetics in cross-circulated whole heart preparations. Laparotomy was performed in 14 Wistar male rats, and abdominal aortic-inferior vena caval shunt was created in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…Allopurinol has also been shown to improve Ca 2ϩ homeostasis and oxidation/nitration of Ca 2ϩ -handling proteins in the tachypacing model in the dog (34) and in the spontaneously hypertensive rat (19). In the present study, there was no change in SERCA protein levels and that of its regulator, PLN, at 8 wk, whereas 12-wk ACF has been reported to have a decrease in SERCA2 expression associated with decreased LV contractility and the response to Ca 2ϩ infusion in the isolated ACF heart (13,36). It is of interest that we found an increase in SLN in ACF LVs that was decreased by allopurinol.…”
Section: Discussioncontrasting
confidence: 54%
“…Allopurinol has also been shown to improve Ca 2ϩ homeostasis and oxidation/nitration of Ca 2ϩ -handling proteins in the tachypacing model in the dog (34) and in the spontaneously hypertensive rat (19). In the present study, there was no change in SERCA protein levels and that of its regulator, PLN, at 8 wk, whereas 12-wk ACF has been reported to have a decrease in SERCA2 expression associated with decreased LV contractility and the response to Ca 2ϩ infusion in the isolated ACF heart (13,36). It is of interest that we found an increase in SLN in ACF LVs that was decreased by allopurinol.…”
Section: Discussioncontrasting
confidence: 54%
“…5D) -extrusion function of NCX1 is facilitated in the present hypertrophied hearts, the O 2 cost of LV contractility might have increased (14,31). A recent study reported that PLM regulates cardiac contractility by modulating NKA and/or NCX1, although at present the mechanism by which PLM regulates cardiac contractility is being actively investigated and is a topic of lively debated (23).…”
Section: Discussionmentioning
confidence: 78%
“…1 in Table 3) to an experimentally obtained series of five to six paired LV P-V data to obtain a set of ESPVR and EDPVR. Thus we determined PVA by subtracting the area under the best-fit EDPVR from the area under the best-fit ESPVR (1,19,31). In the present study, we calculated PVA at mLVV (PVA mLVV) to assess LV mechanical work based on our studies (1,6,19,32,33).…”
mentioning
confidence: 99%
“…The rat model of chronic HF due to volume overload induced by aorto-caval fistula has been previously well characterized [17][18][19]. It shares many similarities with the natural course of human HF including gradual development of the disease that proceeds through a stage of compensated hypertrophy followed by gradual decompensation into the overt HF [19], neurohumoral activation, cardiac output redistribution [20], fluid retention with pulmonary congestion and impairment of myocardial efficiency [21]. On the other hand, volume overload-induced HF has several features distinct from other HF models including a lack of myocardial fibrosis and inflammation [22,23] and involvement of different signalling pathways (upregulation of Akt and Wnt signalling) compared to experimental myocardial infarction or pressure overload [23].…”
Section: Introductionmentioning
confidence: 99%